Analisa Faktor-faktor yang mempengaruhi Keputusan Mahasiswa Memilih Kuliah di Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta - Yusuf Suhardi; Meita Pragiwani; Agustian Burda (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2017)
This research was conducted at Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta. The study population is STEI New Student of academic year 2016/2017 totaling 1,062 people, sampling using Slovin amounted to 295 students of STEI in S1 Accounting Study Program, S1 Management, Accounting D3 and D3 of Trade Management. Sampling technique with random sampling or random. This research uses descriptive analysis method. The result of validity test of internal factor and external factor r-count all bigger than r-table mean all statement is valid. Reliability test results show all statements both internal and external realibel because crobach Alpha is 0.780 and 0.729 above 0.6. The results show that STEI Student Candidates from the beginning of the majority aspire to become an economics graduate. Most of the respondents believe that STEI graduates will get a good job. The majority respondents felt they had a talent in the field of economics. The majority enter STEI because STEI accreditation is B and in deciding place of college majority factor of location that is close to campus, besides because of tuition in STEI is affordable. Suggestion of lectures at STEI which is dominant is advice from parents then from friends. The majority of STEI Student Candidates receive information from brochures and banners, receive very little information from advertisements on newspapers, radio, television, internet and STEI presentations at school